Maultasche og Novillada? En teori for turistordbøger - Leroyer, Patrick (Nordiske Studier i Leksikografi, 2007)
In addition to tourist guides and books, millions of information hungry tourists all around the world use dictionaries referred to as ‘travel dictionaries’, including phrase books containing glossaries and lexicographically structured information. Also, software companies propose multilingual, downloadable dictionary solutions that can be printed on demand or consulted on a PDA or a WAP phone. In brief, the lexicographic commercial supply and demand are enormous. However, no specific lexicographic theory has ever been developed in this field of lexicography which remains scientifically neglected. The purpose of this article is to develop a specific theory for tourist dictionaries and thereby lay the foundation of tourist lexicography as a new field of dictionary research and practice. In order to demonstrate its potential, the theory will be applied to a prototypical tourist dictionary concept. The core of the theory is to bring targeted, useful cognitive data types in tourist dictionaries, in particular cultural words such as ‘Maultasche’ (huge ravioli served in Swabia, Germany) and ‘Novillada’ (corrida for young bulls in Spain and Southern France).